BS24 T1 mapping in a mouse model of myocardial infarction model using variable flip angle manganese enhanced MRI. (6th June 2022) - Janudin, Shahrani; Feng, Zhiping; Tolomeo, Daniele; Lythgoe, Mark; Wells, Jack; Stuckey, Daniel
Abstract : Introduction: T1 mapping is a quantitative MRI approach that calculates the longitudinal relaxation time of the tissue based on the signal amplitude in different T1 weighted images1. Manganese is a clinically relevant T1 contrast medium that enters myocytes via active calcium channels, thereby lowering T1 in viable myocardium2 3. The Lock-looker inversion recovery sequence is the standard method for T1 measurements. However, there are limitations to this technique including long acquisition times and inconsistent T1 estimates. Here we use a Variable Flip Angle (VFA) approach and manganese enhanced MRI (ME MRI) to measure T1 changes post myocardial infarction in mice. Methods: The VFA T1 mapping approach was first validated against phantom samples in vitro. Myocardial infarction was then induced in 6 C57BL/6 female mice. ME MRI was performed 4 days, 11 days, and 63 days after infarction using a 9.4T Bruker system. Bright blood imaging was acquired 30 min after 0.1mmol/kg i.p. MnCl2 using a 3D Intragate (IG) FLASH protocol at flip angles of 2°, 8°, and 14°, with TR/TE=10ms/1.8ms, slab thickness=5mm, FOV=25mm x 25mm, matrix size =128x128x10, bandwidth=98684.2kHz, navigator slice: pulse= 2°, thickness=3mm, bandwidth: 1826.7kHz were used. T1 was estimated using the DESPOT1 protocol. Results: The VFA approach gave similar longitudinal relaxation rates (R1=1/T1) to those acquired using an established saturation recovery method in a manganese phantom containing 0mM, 0.1mM, 0.2mM, 0.5mM and 1.0mM MnCl2 (Figure 1A & B). ME MRI of the infarcted tissue gave higher T1 values than the remote myocardium at all time points as the damaged tissue was unable to uptake manganese (Figure 2). Infarct ME MRI T1 was higher on day 4 than day 11 (P=0.012) which may be due to post infarct inflammatory cell infiltration and oedema facilitating manganese accumulation. Conclusion: The VFA approach can rapidly and accurately measure T1 and when combined with manganese injections can be used to identify the infarcted regions of the myocardium.